SISTEM INFORMASI ADMINISTRASI NILAI SISWA BERBASIS WEB DI MADRASAH TSANAWIYAH NEGERI 2 SEMARANG - Wahyu EY; Zaenal Mustofa (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
The problem of repetitive work done by the homeroom teacher when processing grades around becomes a major problem experienced by every homeroom teacher in school. A good academic system is needed because it can minimize the work of homeroom teacher. MTs Negeri 2 Semarang in the processing of reporting value data is still using the conventional way by filling in the value legers. The teaching teacher fills in the value data to grade according to subjects. Then the homeroom teacher is reported in the form of grades per subject. Then from the value data per subject the homeroom teacher must reprocess it into grades per student and print it. This will be a repetitive job if the homeroom teacher also serves as a teacher. Reporting is still using copy paste from flash to flash which is very risky of losing data. This is compounded by the school building which is divided into two buildings with a considerable distance between the old building and the new building that makes teachers feel reluctant to report grades. To solve the existing problems, the authors propose a web-based value data administration system in MTs Negeri 2 Semarang that will facilitate teachers in processing and reporting value data. The program is expected to be able to deal with existing problems and ease the work of homeroom teachers.